Plasma CD59 concentrations are increased in preeclampsia with severe features and correlate with laboratory measures of end-organ injury (2020)
ABSTRACT Objectives: Dysregulation of CD59 may lead to increased complement-mediated end-organ injury in preeclampsia. We sought to determine if soluble CD59 concentrations are altered in preeclampsia with severe features. Study design: Observational case-control study, which enrolled subjects prospectively from six centers in Colombia from 2015 to 2016. Cases had preeclampsia with severe features and controls were either healthy or had chronic hypertension, gestational hypertension, or preeclampsia without severe features. Trained coordinators collected clinical data, blood and urine. Analyses were by test of medians and Spearman’s correlation. Main outcome measures: Soluble CD59 concentration in plasma and urine, using enzyme linked immunosorbent assays. Results: In total, 352 subjects were enrolled (104 cases; 248 controls). Compared to healthy women or those with other hypertensive disorders of pregnancy, women with preeclampsia with severe features had increased concentration of CD59 in plasma (P < 0.001) and decreased CD59 in urine (P = 0.01). In sub-group analyses, plasma CD59 concentrations were increased in preeclampsia with severe features compared to healthy controls (P <0.001) or controls with either chronic hypertension (P = 0.002) or gestational hypertension (P = 0.02). Increased plasma CD59 concentrations correlated with decreased platelet count and increased lactate dehydrogenase, creatinine, aspartate transaminase, urine protein/creatinine ratio, systolic blood pressure and diastolic blood pressure (P < 0.01, all correlations). Conclusion: In women with preeclampsia with severe features, soluble CD59 concentrations were increased in plasma and decreased in urine, and plasma levels correlated with increased blood pressure and end-organ injury. Soluble CD59 concentrations may help identify a subset of women with preeclampsia that have altered regulation of terminal complement proteins.